Um estudo sobre ferramentas de intrusão em ambientes computacionais: um mapeamento sistemático - Ramos, David Gleyson (Brasil, 2021)
With the increase of cyber attacks on large companies and government entities, it became essential to take the necessary security measures. In this work, the focus is to address the main tools used by attackers and professionals who perform intrusion tests, as a consequence, to present the main attacks from these tools. The research methodology adopted is based on the principles of Experimental Software Engineering, which is based on conducting a secondary study: Systematic Mapping. The results reveal the most frequent tools and attacks and the paths that are dealt with by these individuals or groups.